Relationship of phubbing with depression, anxiety, self- esteem and other mental variables - Karslı, Feyza; Açık Yavuz, Begüm (Journal of Dependence, 2024)
Objective: The aim of this study is to examine the relationship phubbing behavior, mood, self-esteem, life satisfaction and mental disorders.Method: The population of the research consists of people over the age of 18 and using smart phone. A total of 134 people participated in the research. The data collection process was carried out both face-to-face and online. Data collection tools are "General Sociothelist Scale", "Positive and Negative Affect Scale", "Depression Anxiety Stress Scale" and "Personal Information Form" which includes questions about demographic information and the level of satisfaction of the participants with themselves and their lives.Results: Depression mean score was 5.84, anxiety mean score was 4.60, stress mean score was 8.01, negative affect mean score was 23.01, positive affect mean score was 34.25, and phubbing mean score was 44.98. A statistically significant and positive correlation was found between phubbing and depression, anxiety, stress and negative affect scores. In addition, according to the predictive model, phubbing scores explain 4% of the variance in negative affect scores, 5% of the variance in anxiety scores, 7% of the variance in depression scores, and 12% of the variance in stress scores.Conclusion: Phubbing is inversely related to depression, anxiety, stress and negative mood and has a share in explaining all these mental health determinants
Keywords: Phubbing; mental health; mental disorders; mood; self-esteem; life satisfaction